Pruning as a strategy to improve the nutritional value of the aerial parts of industry- purpose cassava clones - FERNANDES,Francisco Duarte (2020)
ABSTRACT The present study aimed to assess the influence of pruning on the starch yield and nutritional value of the aerial parts of industry- purpose cassava clones adapted to the Cerrado region of Central Brazil. Four elite clones were submitted to either total shoot pruning or no pruning at 12 months after planting, in a randomized complete block design with three replications. Plants were evaluated eighteen months after planting. Clone 330/09 presented the highest root yield with and without pruning, and also higher starch yield, green and dry mass yields, and crude protein yield of aerial parts without pruning. In plants that were pruned, clones 117/09 and 359/09 stood out, with higher yields of the crude protein content of the aerial part and a higher in vitro digestibility of the dry matter. These clones are therefore an option when using the aerial parts of cassava in animal feed. Total pruning at 12 months of age significantly increased the crude protein content and in vitro digestibility of the dry matter of the aerial parts, improving its nutritional value. Pruning did, however, reduce the starch yield of the roots and the total yields of the roots and aerial parts.